Impact of Limb Salvage on Prognosis of Patients Diagnosed With Extremity Bone and Soft Tissue Sarcomas - Yu, Kaixu; Chen, Ying; Song, Kehan; Xiong, Fanxiu; Tian, Yahao; Guan, Hanfeng; Li, Feng (Frontiers in Oncology, 2022)
Background Although clinicians and patients with extremity bone and soft tissue (EBST) are increasingly interested in limb salvage surgery (LSS), because of the minimal damage to physical appearance and function, however, there is still a lack of large-scale population studies on whether LSS improves the prognosis of patients. Purpose The aim of this study was to compare the survival of patients with EBST sarcomas after receiving LSS and amputation. Methods To conduct the population-based study, we identified 6,717 patients with a histologically diagnosed bone sarcoma and 24,378 patients with a histologically diagnosed soft tissue sarcoma from the Surveillance, Epidemiology, and End Results database. We analyzed overall survival (OS), cancer-specific survival (CSS), and non-sarcoma survival (NSS) using the Kaplan–Meier method, log-rank test or Gray test, Cox regression model, propensity score-matched analysis, and landmark analysis. Results LSS could improve the prognosis in patients with most EBST subtypes, except for Ewing sarcomas and MPNST. However, in the subgroup without distant metastases, limb salvage increased CSS only for patients with osteosarcoma, Ewing sarcoma, and leiomyosarcoma, as well as NSS for patients with chondrosarcoma and synovial sarcoma. Landmark analysis further demonstrated that sarcoma survivors surviving <10 years could benefit from LSS but not for long-term survivors ≥10 years. Moreover, for patients with distant metastases, LSS could improve survival of osteosarcoma patients but worsen CSS among patients with MPNST. Landmark analysis further demonstrated that LSS improved survival among osteosarcomas patients with distant metastases only within 1 year after surgery. Moreover, patients receiving LSS and those receiving amputation had a high risk of dying from different non-sarcoma diseases during the postoperative follow-up. Conclusions The impact of limb salvage on the prognosis of patients depends on the pathological subtype and stage of EBST sarcomas.